Der Vereinssport in den Städten Oberhausen und Mülheim an der Ruhr. Eine exemplarisch vergleichende Untersuchung sozialer Strukturen und Ungleichheiten unter besonderer Berücksichtigung des Kinder- und Jugendsports. - Beyer, Saskia (My University, 2020)
Der Vereinssport in Oberhausen wird insbesondere in seiner sozialräumlichen Differenzierung und hinsichtlich sozialer Ungleichheit untersucht. Als wichtige Dimensionen vertikaler sozialer Ungleichheit, die sich auch im Vereinssport widerspiegeln können, werden Bildung, Einkommen und Vermögen, Gesundheit untersucht. Bei der Untersuchung der Sozialräume der Städte Oberhausen und Mülheim waren deutliche Unterschiede zwischen Stadtteilen festzustellen, die sich auch in sportlichen Strukturen widerspiegeln. Zentrales Ergebnis obiger Analysen ist ein Nord-Süd-Gefälle in Oberhausen mit Defiziten des Südens (Alt-Oberhausen und teils Osterfeld) im Vergleich zum Sterkrader Norden. In Mülheim ist hingegen der Norden (Styrum, Dümpten, Altstadt Nord) gegenüber dem Süden (besonders Saarn, Menden-Holthausen) benachteiligt. Die Altersstruktur der Sportvereinsmitglieder in den beiden Städten wird dargestellt und verglichen. Ebenso wird die Geschlechtsstruktur der Sporttreibenden sowohl innerhalb der Altersklassen als auch im Vergleich der Städte behandelt. Da die Arbeit den Jugendsport besonders berücksichtigt, hat sich eine Befragung von Jugendlichen angeboten, um einen Einblick zu erhalten. Dabei wurde die Altersgruppe 15 -18 ausgewählt, differenziert nach den Schulformen des gegliederten Schulsystems. Die Untersuchung bestätigt die Bedeutung von Bildung. Bildung ist der Schlüssel zur Bekämpfung sozialer Ungleichheit - auch im Sport.

This thesis aims to examine and compare the impact of socio-spatial differences and social inequalities on club sports in Oberhausen, Germany, with the city of Mulheim an der Ruhr (Mülheim), Germany. Being important dimensions of vertical social inequality, education, income, and health are herein examined, followed by a short analysis of horizontal dimensions of inequality in both cities. Age and gender structures within sports clubs are also presented and analysed. Additionally, a survey of attitudes towards club sports amongst youth is provided. Oberhausen is located in the west of the Ruhrgebiet. Its neighbouring cities are Bottrop in the north, Dinslaken and Duisburg in the west, Essen in the east, and Mülheim in the south. Present-day Oberhausen was created through the amalgamation of three smaller towns: Alt-Oberhausen, Sterkrade, and Osterfeld. These anthropogeographical conditions reflect the population’s use of space, which outline important premises for physical exercise and the chosen locations of sports facilities. When studying the social spaces of Oberhausen and Mülheim an der Ruhr, there were clear differences between districts, which are further reflected in sports structures. The results of this analysis reveal a north-to-south downhill deficiency gradient from the southern sectors, Alt-Oberhausen and parts of Osterfeld, to the northern sector, Sterkrade. In Mülheim, however, it is the northern sectors of Styrum, Dümpten, and Alstadt Nord compared to the southern sectors of Saarn and Menden-Holthausen which are disadvantaged. In Oberhausen, 37 sports can be practiced in club settings. An overview of each sport is provided including club names and numbers, membership numbers, and conspicuous age and gender structures, which are then taken into account when comparing Oberhausen and Mülheim. Furthermore, it will be tested whether the variety of sports offered is influenced, or even shaped, by gender in both cities. It is already apparent that equestrianism, volleyball, gymnastics, and dance are dominated by women, whereas wrestling, fishing, billiards, and chess are dominated by men. Because this paper particularly considers child and youth sports, a survey of adolescents has been provided in order to obtain insight into their attitudes regarding sports. The age group 15 to 18 years old was selected according to statistic gathered by the Landessportbund Nordrhein-Westfalen and is broken down into further subsections according to school types in the structured school system. The results of this survey provide information concerning the extent of participation in sports, whether in clubs or free time, or a lack of physical activities, as well as the reasons attributed to it. In addition, the impact of class affiliation and migration background on club sports as well as the preference or disapproval of certain sports are presented. While stratigraphic educational deficits are often associated with specific features and deficits in sports participation, these are essentially only noticeable in female migrants. Finally, measures taken against social inequality in club sports in both Oberhausen and Mülheim are here presented. The present study confirms the importance of education. Education is the key to fighting social inequality, even in sports.
Club Sports in Oberhausen and Mülheim an der Ruhr. A comparative study on social structures and inequalities with special attention to child and youth sports.
Keywords: Sport; Sportverein; Soziale Ungleichheit; Sozialraumanalyse; Räumliche Disparität; Sozialstruktur; Bildungsangebot; Sportart; Freizeitaktivität; Jugendlicher; Altersstruktur; Schulsystem; Städtevergleich; Vereinssport; Bildungsbeteiligung